A retrospective clinical and epidemiological analysis of cases of hepatitis E in St. Petersburg - H. D. Peradze; E. V. Esaulenko; E. Y. Malinnikova; M. I. Mihaylov (Журнал инфектологии)
Hepatitis E – zoonotic disease that has received a nosological independence twenty years ago, when Russian scientist, Professor M.S. Balayan, identified the pathogen (hepatitis E). It was believed that the disease can manifest itself only in the acute form, and occur only in regions with subtropical and tropical climate conditions. The development and introduction of practicing of modern scientific research methods for detecting antibodies to activator change, to view the global prevalence of infection and present doubts on inabilities of transformation into a chronic f a retrospective analysis of hospital cases of acute jaundice hepatitis E in Saint-Petersburg.Etiologic accessory to hepatitis E implemented by discovery in serum of patients a specific marker of infection hepatitis E – an anti-HEV.In the analysis of archive documentation for 2000–2011 from the patients which were hospitalized in the Clinical Infectious Diseases Hospital by S.P. Botkin only 11patients were diagnosed with «acute hepatitis E». Which indicates the presence of patients with acute hepatitis E infection among hospitalized in hospitals of the city of St. Petersburg are not endemic for this disease. The presence of cases of disease of the indigenous inhabitants of the city during the past years, which isn’t going beyond its limits, indicates the existence of «autochthonous» hepatitis E.